Infection prevention and control (IPC) at a Lassa fever treatment center before and after the implementation of an intensive IPC program - Olayinka Stephen Ilesanmi; Oladele Olufemi Ayodeji; Ayobami A. Bakare; Nelson Adedosu; Anthonia Adeagbo; Adedamola Odutayo; Felix Olugbenga Ayun; Ayomide E. Bello (Journal of Ideas in Health, 2020)
Background: Infection prevention and control (IPC) programs are important to control the Lassa Fever (LF) outbreak. We reported IPC's status at the Federal Medical Centre, Owo, southwest Nigeria, before and after implementing the IPC program during a surge in the LF outbreak. Methods: We conducted a longitudinal observational study among five health care professionals at the Federal Medical Centre, Owo, between February 2019 and May 2019 using the IPC Assessment Framework (IPCAF). The tool has eight core components with a score of 0-100 per component and provided a baseline assessment of the IPC program and evaluation after three months. We interviewed relevant unit heads and IPC committee members in the first phase. In the second phase, we designed and implemented the IPC program, and in the third phase, we conducted a repeat interview similar to the first phase. The program initiated included training healthcare workers and providing relevant IPC items according to identified gaps and available funding. Results: We interviewed five health care professionals, two female nurses, and three male doctors responsible for organizing and implementing IPC activities at the Federal Medical Centre, Owo, with an in-depth understanding of IPC activities. The overall IPC level score increased from 318.5 at baseline to 545 at three months later. IPC improvements were reported in all the components, with IPC education and training [baseline (20), final (70)], IPC guidelines [baseline (50), final (92.5)] and monitoring/audits of IPC practices and feedback [baseline (40), final (82.5)] recording the highest improvements. Healthcare-associated infection [baseline (10), final (25)], and built environment, materials, and equipment for IPC [baseline (43.5), final (55)] had the least improvement. Poor motivation to adopt recommended changes among hospital staff were major issues preventing improvements. Conclusion: Promotion of IPC program and activities should be implemented at the Federal Medical Centre, Owo. References World Health Organization, WHO. Lassa fever. Available from: https://www.who.int/health-topics/lassa-fever/#tab=tab_1. [Accessed on 11 October 2020] Nigeria Centre for Disease Control. Lassa fever. Available from: https://ncdc.gov.ng/diseases/factsheet/47. [Accessed on 11 October 2020]. World Health Organization, WHO. Lassa fever. Available from: https://www.who.int/news-room/fact-sheets/detail/lassa-fever. [Accessed on 11 October 2020]. Ijarotimi IT, Ilesanmi OS, Aderinwale A, Abiodun-Adewusi O, Okon IM. Knowledge of Lassa fever and use of infection prevention and control facilities among health care workers during Lassa fever outbreak in Ondo state, Nigeria. Pan Afr Med J. 2018; 30:1-13. https://doi.org/10.11604/pamj.2018.30.56.13125 Mateer EJ, Huang C, Shehu NY, Paessler S. Lassa fever–induced sensorineural hearing loss: A neglected public health and social burden. PLoS Negl Trop Dis. 2018;12(2):1-11. https://doi.org/10.1371/journal.pntd.0006187 Ijarotimi I., Oladejo J., Nasidi A, Jegede O. Lassa fever in the State Specialist Hospital Akure, Nigeria: Case report, Contact tracing and outcome of hospital contacts. Int J Infect Trop Dis. 2016;3(1):20-28. https://doi.org/10.14194/ijitd.3.1.4 Ireye F, Ejiyere H, Aigbiremolen AO, Famiyesin OE, Rowland-Udoh EA, Ogeyemhe CO, Okudo I, Onimisi AB. Knowledge, attitude and infection prevention and control practices regarding Lassa fever among healthcare workers in Edo State, Nigeria. Int J Prev Treat. 2019;8(1):21-27. https://doi.org/10.5923/j.ijpt.20190801.03 World Health Organization. Infection prevention and control assessment framework at the facility level. 2018; 2016:1-15. Available from: https://www.who.int/infection-prevention/tools/core-components/IPCAF-facility.PDF?ua=1 [Accessed on 11 October 2020]. World Health Organization, WHO. Communicable disease surveillance and response systems - Guide to monitoring and evaluating. Epidemic and pandemic alert and response. Published online 2006:90. doi: rr5305a1 [pii] Ousman K, Kabego L, Talisuna A, Diaz J, Mbuyi J, Houndjo B, et al. The impact of Infection Prevention and control (IPC) bundle implementation on IPC compliance during the Ebola virus outbreak in Mbandaka/Democratic Republic of the Congo: A before and after design. BMJ Open. 2019;9(9):1-6. https://doi.org/10.1136/bmjopen-2019-029717 Nzinga J, Mbindyo P, Mbaabu L, Warira A, English M. Documenting the experiences of health workers expected to implement guidelines during an intervention study in Kenyan hospitals. Implement Sci. 2009;4(1):1-9. https://doi.org/10.1186/1748-5908-4-44. Ataiyero Y, Dyson J, Graham M. Barriers to hand hygiene practices among health care workers in sub-Saharan African countries: A narrative review. Am J Infect Control. 2019 May;47(5):565-573. https://doi.org/10.1016/j.ajic.2018.09.014. Gilbert GL, Kerridge I. The politics and ethics of hospital infection prevention and control: a qualitative case study of senior clinicians’ perceptions of professional and cultural factors that influence doctors’ attitudes and practices in a large Australian hospital. BMC Health Serv Res. 2019; 19(212). https://doi.org/1186/s12913-019-4044-y.